Introducing Remote Enculturation: Learning Your Heritage Culture From Afar. (7th April 2016) - Ferguson, Gail M.; Costigan, Catherine L.; Clarke, Christy V.; Ge, Julianna S.
Abstract: Can youth living outside their heritage country become enculturated from afar via avenues of modern globalization? In this article, we expand the theory of how heritage cultural socialization occurs in transnational families by introducing the construct of remote enculturation as a modern form of cultural transmission. Remote enculturation falls within the cultural socialization category of ethnic/racial socialization and is a form of enculturation that involves learning aspects of one's heritage culture via indirect or intermittent exposure, or both. We compare and contrast remote enculturation with traditional enculturation, proposing that self‐initiated remote enculturation, in particular, has strong ties with the development of identity. Research on immigrants' consumption of foreign media and on parenting international adoptees supports remote enculturation as a distinct avenue of cultural learning, as do the experiences of youth from immigrant families. We conclude with a research agenda to empirically evaluate the construct of remote enculturation.